Pareto analysis: Diagnosing investments in managerial ego - C. G. Robinson (South African Journal of Business Management, 1983)
Managers frequently state that 80% of profits or sales are derived from 20% of the product range. Though lip service is paid, the concept often is not applied as a tool for resource allocation and discrimination between a portfolio of products or business units. This article explains how managers can use the technique of Pareto analysis to identify different strategic categories as a guide to the allocation of resources and management attention.
Keywords: 650